Edge intelligence enabled Internet of Things - Li, Shancang (EAI Endorsed Transactions on Internet of Things, 2020)
The IoT provides billions of smart devices connectivity to the Internet, which drives a number of promising applications range from smart home to the artificial intelligence (AI) enabled vehicle-to-everything (V2X).This editorial will introduce the emerging edge intelligence enabled IoT systems, including smart home, QRbased indoor navigation system, dyslexia monitoring system, and wearable device tracing against the COVID-19.